2018
DOI: 10.1097/md.0000000000013172
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis with refractory hypokalemia

Abstract: Rationale:Renal tubular acidosis (RTA) represents a class of metabolic disorders characterized by metabolic acidosis with a normal plasma anion gap. As a rare complication of primary biliary cirrhosis (PBC), RTA is easily overlooked, likely leading to misdiagnosis.Patient concerns:A 32-year-old woman who had been diagnosed with PBC at our hospital was found to have hypokalemia due to repeated fatigue for 2 years, and the etiology was unknown.Diagnoses:Due to the laboratory test results, radiographic findings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Aiming for a better understanding of the disease, we performed a search of the PubMed database using MeSH descriptors (Acidosis, Renal Tubular; Lupus Erythematosus, Systemic; Sjogren’s Syndrome, Systemic Vasculitis, Rheumatoid Vasculitis, Arthritis, Rheumatoid, Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis, Churg-Strauss Syndrome, IgA Vasculitis, Spondylitis, Ankylosing, Cryoglobulins, Hepatitis, Autoimmune, Liver Cirrhosis, Biliary), and we identified 37 individual case reports published since December 2016 with the association of distal renal tubular acidosis and the following autoimmune disorders: SLE, Sjögren’s syndrome, autoimmune hepatitis, primary biliary cirrhosis and rheumatoid arthritis (see Table 1 ) [ 6 , 10 , 11 , 13 , 15 , 16 , 17 , 18 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. We also identified a case of hereditary autoimmune polyendocrine syndrome (DRTA, hypoparathyroidism, Addison disease), published in a series of cases, which was not included in our analysis, due to the lack of individual data availability [ 39 ].…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming for a better understanding of the disease, we performed a search of the PubMed database using MeSH descriptors (Acidosis, Renal Tubular; Lupus Erythematosus, Systemic; Sjogren’s Syndrome, Systemic Vasculitis, Rheumatoid Vasculitis, Arthritis, Rheumatoid, Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis, Churg-Strauss Syndrome, IgA Vasculitis, Spondylitis, Ankylosing, Cryoglobulins, Hepatitis, Autoimmune, Liver Cirrhosis, Biliary), and we identified 37 individual case reports published since December 2016 with the association of distal renal tubular acidosis and the following autoimmune disorders: SLE, Sjögren’s syndrome, autoimmune hepatitis, primary biliary cirrhosis and rheumatoid arthritis (see Table 1 ) [ 6 , 10 , 11 , 13 , 15 , 16 , 17 , 18 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. We also identified a case of hereditary autoimmune polyendocrine syndrome (DRTA, hypoparathyroidism, Addison disease), published in a series of cases, which was not included in our analysis, due to the lack of individual data availability [ 39 ].…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
“…In only one case out of these 33 reports, cyclophosphamide was used, with eGFR improvement and potassium value amelioration [ 33 ]. Immunosuppressive therapy was not used in those three cases of autoimmune hepatitis, primary biliary cirrhosis and rheumatoid arthritis included in our analysis [ 36 , 37 ]. A meta-analysis published in 2021 which included patients with renal tubular acidosis and liver pathology (autoimmune hepatitis and alcoholic hepatitis) showed that corticosteroids improved short term mortality in this group, but it is not mentioned any effect on the evolution of DRTA [ 55 ].…”
Section: Treatment and Outcomementioning
confidence: 99%